DETERMINANTS OF FOREIGN DIRECT INVESTMENT IN INDONESIA - Fradya Randa & Hasdi Aimon (International Journal of Research Science and Management, 2018)
The aim of this study is to examine the short-term and long-term relationship as well as explain the determinants of the flow of foreign direct investment (FDI) in Indonesia. The analysis models used were cointegration by Johansen-Juselius and error correction model (ECM). A time series data from the period of 1982 to 2016 was used. The findings of this research state that the decision of foreign investors to invest in the long term is positively influenced by currency exchange rate and money supply, and negatively by inflation and trade openness. In addition, the findings show a positive relationship between market size, exchange rate and money supply to FDI inflows in the short term.